2022
DOI: 10.1007/s10482-021-01706-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cultivable bacteria from deep-sea sediments of the Colombian Caribbean and their potential in bioremediation

Abstract: The diversity of deep-sea cultivable bacteria was studied in seven sediment samples of the Colombian Caribbean. Three hundred and fty two marine bacteria were isolated according to its distinct morphological character on the solid media, then DNA sequences of the 16S rRNA were ampli ed to identify the isolated strains. The identi ed bacterial were arranged in three phylogenetic groups, Firmicutes, Proteobacteria, and Actinobacteria, with 34 different OTUs de ned at ≥97% of similarity and 70 OTUs at ≥98.65%, be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Pseudomonadota has been described as the most common phylum in several sediment samples from marine environments [63,64]. Moreover, metagenomic analysis of sediment samples collected in the Colombian Caribbean region had also found Proteobacteria along with Bacteriodetes (Bacteroidota), Actinobacteria (Actinomycetota), and Firmicutes (Bacillota) as the dominant phyla, while Pseudomonas were the most common genera [78,79]. The genera Enterobacter and Stenotrophomonas have been documented in marine samples from around the world [63,80].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonadota has been described as the most common phylum in several sediment samples from marine environments [63,64]. Moreover, metagenomic analysis of sediment samples collected in the Colombian Caribbean region had also found Proteobacteria along with Bacteriodetes (Bacteroidota), Actinobacteria (Actinomycetota), and Firmicutes (Bacillota) as the dominant phyla, while Pseudomonas were the most common genera [78,79]. The genera Enterobacter and Stenotrophomonas have been documented in marine samples from around the world [63,80].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that microorganisms that degrade hydrocarbons create lipolytic enzymes such as lipases. Blandon et al [ 154 ] identified 56 lipolytic enzyme-producing bacteria in the deep-sea sediments of the Colombian Caribbean and discussed their bioremediation potential [ 154 , 155 ].…”
Section: Role Of Lipases In Bioremediationmentioning
confidence: 99%
“…Three phylogenetic groups were found: Proteobacteria, Actinobacteria and Firmicutes. This information gives an estimation of the phylogenetic diversity and provides a first step to the creation of taxonomic inventories from existing microbial populations with bioremediation capacity (Blandón et al 2022).…”
Section: Bioremediation In Colombiamentioning
confidence: 99%